Aid, Protection, and Social Alliance: The Role of Jewelry in the Margins of the Hours of Catherine of Cleves. (20th November 2018) - Decker, John R.
Abstract: This article examines five miniatures in the "Hours of Catherine of Cleves" (completed 1442), each containing representations of jewelry in the margins, which operate on two different levels. First, they demonstrate Catherine of Cleves's adoration of five female saints. I argue that the fictive jewelry may be understood as simulated ex-votos designed to secure the aid and protection of the saints. Second, the images establish strategic alliances with each saint. As a final dimension, I explore how the vitae of these saints may have had resonances for the duchess that help explain the focus placed on them in the manuscript.